Selective activity of 2,4-diaryl-1,2,3,4-tetrahydroquinolines on Trypanosoma cruzi epimastigotes and amastigotes expressing β-galactosidase (2013)
The growth inhibitory effect on Trypanosoma cruzi epimastigotes and the unspecific cytotoxicity over NCTC-929 fibroblasts of two series of previously synthesized 2,4-diaryl-1,2,3,4-tetrahydroquinolines (THQ), have been studied in vitro and compared with those of benznidazole (BZ). Derivatives AR39, AR40, AR41, AR91 and DM15 achieved outstanding selectivity indexes (SI) on the extracellular form (SITHQ > SIBZ > 9.44) and thus, were tested in a more specific in vitro assay against amastigotes, showing less effectiveness than the reference drug (SIBZ > 320) but also accomplishing great selectivity on the intracellular stage (SITHQ > 25). These promising results, supported by the in-silico prediction of high bioavailability and less potential risk than benznidazole, reveal several tetrahydroquinolines as prototypes of potential antichagasic drugs.